1 Applying improvement to the co-creation of quality. (29th July 2022) - Shah, Amar
Abstract : Introduction: A 5 year retrospective study of all quality improvement projects at East London NHS FT found that QI projects that involved service users as full and equal members of the team were 2.8 times more likely to be successful. 1 This led to us applying quality improvement in a robust way to help develop and test ideas to ensure the 'Big I' of full, authentic involvement of patients/service users was integral to all our QI work. Methods: Below is the theory of change developed by service users, QI coaches with lived experience and quality improvement in partnership: The ideas that were developed are being tested across different parts of the organisation, to help us learn what enables true, authentic and meaningful involvement of patients in quality improvement activities. There is a steering group for this work, with service users and quality improvement involved. The ideas are being tested through a number of local quality improvement projects, often led by service users. Results: The control chart below shows the percentage of all quality improvement projects that demonstrate the Big I of true, authentic partnership between service users and staff throughout the QI endeavour: Through this work, a number of key findings have been identified which can enable teams to authentically involve patients and service users from the outset of QI projects in a meaningful way. This session would present the key learnings so far, which are immediately translatable to all healthcare settings. Discussion: Authentic, meaningful partnership with patients and service users in our quality improvement efforts gives us a 3 times greater likelihood of the improvement being successful. It also offers us the opportunity to better understand the system and develop better ideas from those with lived experience. Applying quality improvement to the complex challenge of how to involve patients in this way reliably, for every QI project, has helped us learn a number of important elements that are required in order to effectively involve and support patients to partner in our improvement efforts. Reference: Kostal G, Shah A. Putting improvement in everyone's hands: opening up healthcare improvement by simplifying, supporting and refocusing on core purpose. British Journal of Healthcare Management 2021. https://doi.org/10.12968/bjhc.2020.0189